HUBUNGAN TINGKAT PENGETAHUAN SEKSUAL PRANIKAH DENGAN PERILAKU SEKSUAL - Dewi Nurul Sari (Akademi Kebidanan La Tansa Mashiro, 2013)
The aim of this study is to know correlative between knowledge concerning about secual premarital towards sexual behavioral at students class XI of 1st Senior High School Of Kesatrian Semarang in 2009. This research work at 1st Senior High School of Kesatrian Semarang, amounting to 78 respondents and analysis using chi square. Result of this research there is correlation between knowledge concerning about sexual premarital towards sexual behavioral at students class X1 of 1st Senior High School of Kesatrian I Semarang IN 2009.